Pengaruh Model Project Based Learning terhadap Kompetensi Praktikum Sensor dan Transduser Ditinjau dari Kreativitas, Motivasi Belajar, dan Kemandirian Belajar Mahasiswa - Nur Athiyyah Fadhilah; A.Muzawwirah Patawari (Jurnal Elektronika Telekomunikasi & Computer, 2026)
This study aims to determine the effect of the Project Based Learning (PjBL) model on students’ practical competencies in sensors and transducers practicum. The study employed a quantitative approach using an ex post facto method. The independent variables consisted of project planning (X1), team collaboration (X2), and project creativity (X3), while the dependent variable was students’ practical competence in sensors and transducers (Y). The research subjects were 20 students from the Vocational Mechatronics Education Study Program. Data collection techniques included observation, score documentation, and project assessment rubrics. Data analysis was conducted using descriptive statistics and multiple linear regression analysis. The results showed that the Project Based Learning model had a positive effect on students’ practical competence in sensors and transducers. The average posttest score increased significantly compared to the pretest score, with an average pretest score of 49.35 and a posttest score of 92.67. The project creativity variable was found to have the most dominant influence on students’ practical competence. Simultaneous testing indicated a significance value of 0.000 < 0.05, meaning that all independent variables significantly affected students’ practical competence in sensors and transducers. The implementation of PjBL was able to improve practical skills, collaboration, problem-solving abilities, and students’ skills in utilizing Arduino and ESP32-based sensors.